Dietary creatine monohydrate supplementation - Jacobs, I. (Canadian Journal of Applied Physiology, 1999)
This paper summarizes and interprets the research published about physiological aspects of dietary supplementation with creatine monohydrate and the effects on physical performance. A nitrogenous molecule that occurs naturally in the flesh consumed by meat-eaters, creatine is also synthesized endogenously and is stored primarily in skeletal muscle. The research literature in which direct measurements of muscle creatine content have been reported indicates that most, but not all, subjects respond to Òcreatine loadingÓ by increasing the total intramuscular concentration of creatine, including the concentration of phosphocreatine. The factors that affect muscle creatine stores are reviewed, as are the widely ranging results on physical performance. The mechanism of action by which increased intramuscular creatine could enhance performance is not yet clear. Original speculation was that increased phosphocreatine levels prior to commencing exercise, in conjunction with higher free creatine concentration, would prolong the time required until performance-limiting levels of phosphocreatine were reached during intense exercise. It was also speculated that restoration of phosphocreatine levels between bouts of such exercise would be more rapid. More recent studies question such speculation. This review includes a discussion of what is known about the health risks and side-effects associated with creatine loading. The paper concludes with speculation about the unprecedented attention given to creatine supplementation by recreational and competitive athletes and the media.